Governance Services Against Pandemic Covid 19 as a Form of Good Governance - Suhartoyo Suhartoyo (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2020)
Abstract The government service against the Pandemic has been globally planned, measured and well-organized in the world. The Government services also has been the pillar of terms from the good of governance itself, which means every government in the state should perform its role as the extension of people’s hand responsibility to the society environment, honestly, and the effectively of working to create a good implementation against this pandemic. Thus, we should clearly understand that in every governance services against the pandemic is it related or not to the implementation of good governance. So, the purpose of this study is to elaborate the application of the good governance services during this pandemic, so that we will be able to understand widely all about the good governance principle. Keywords: The Governance Service, Implementation as the Good Governance Abstrak Layanan pemerintah melawan Pandemi telah direncanakan secara global, terukur, dan dikelola dengan baik di dunia. Layanan Pemerintah juga telah menjadi pilar istilah dari kebaikan tata kelola itu sendiri, yang berarti setiap pemerintah di negara bagian harus menjalankan perannya sebagai perpanjangan tanggung jawab tangan rakyat terhadap lingkungan masyarakat, secara jujur, dan secara efektif bekerja untuk menciptakan implementasi yang baik terhadap pandemi ini. Dengan demikian, kita harus memahami dengan jelas bahwa dalam setiap layanan tata kelola terhadap pandemi itu terkait atau tidak dengan penerapan tata kelola yang baik. Jadi, tujuan dari penelitian ini adalah untuk menguraikan penerapan layanan tata kelola yang baik selama pandemi ini, sehingga kita akan dapat memahami secara luas semua tentang prinsip tata kelola yang baik. Kata Kunci: Layanan pemerintah, pengembangan tata kelola pemerintah yang baik